2015
DOI: 10.3389/fvets.2015.00075
|View full text |Cite
|
Sign up to set email alerts
|

Steering Endogenous Butyrate Production in the Intestinal Tract of Broilers as a Tool to Improve Gut Health

Abstract: The ban on antimicrobial growth promoters and efforts to reduce therapeutic antibiotic usage has led to major problems of gastrointestinal dysbiosis in livestock production in Europe. Control of dysbiosis without the use of antibiotics requires a thorough understanding of the interaction between the microbiota and the host mucosa. The gut microbiota of the healthy chicken is highly diverse, producing various metabolic end products, including gases and fermentation acids. The distal gut knows an abundance of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 91 publications
3
88
0
1
Order By: Relevance
“…Members of this family have been linked to obesity in humans (Cho et al, 2012), mainly due to the association of many species within the group with the production of butyric acid (Duncan et al, 2002). Ruminococcaceae has been reported to play the role of biohydrogenation, and is capable of producing butyrate via fermenting various substrates, which may exert potential physiological functions in host health (Huws et al, 2011; Onrust et al, 2015). Kim et al (2012) observed that Ruminococcaceae was enriched in mice fed high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Members of this family have been linked to obesity in humans (Cho et al, 2012), mainly due to the association of many species within the group with the production of butyric acid (Duncan et al, 2002). Ruminococcaceae has been reported to play the role of biohydrogenation, and is capable of producing butyrate via fermenting various substrates, which may exert potential physiological functions in host health (Huws et al, 2011; Onrust et al, 2015). Kim et al (2012) observed that Ruminococcaceae was enriched in mice fed high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that intestinal health problems have been partly masked by the routine use of AGPs and that, paradoxically, it is increasing the use of antibiotics on therapeutic administration (antibiotic therapy) (Huyghebaert, Ducatelle, & Van Immerseel, ). In the European Union, the use of AGPs was banned in 2006 while, in the United States, the Center of Veterinary Medicine of the Food and Drug Administration, issued a document in 2012 (“Guidance for Industry”) recommending that antibiotics should be used only in case of specific diseases and not for growth promotion (Onrust et al, ). In chicken production, antibiotic therapy as a management tool consists of administering specific drugs during a limited period, which is important for controlling certain diseases caused by harmful bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…While 16S rRNA sequencing and metagenomics can yield information on abundances of taxa and abundances of genes encoding functional activities, including DNA biomarker estimation (Segata et al, 2011), information on gene expression but especially on microbial metabolic profiles in the intestine will be essential to understand microbiota-host interplay in the gut. Products from polysaccharide fermentation (mainly lactate, shortchain fatty acids and gases) have been well studied in relation to intestinal health (Havenaar, 2011;Russell et al, 2013;Onrust et al, 2015). This is not the case for products from protein and fat degradation, although beneficial effects of, for example, indole, which is formed during degradation of tryptophan, are well described.…”
mentioning
confidence: 99%
“…The use of a complex of probiotic strains, which operate as a network to feed each other or produce different agonistic end metabolites, should be considered. Butyrate production is the most well-known example of a beneficial endproduct (Onrust et al, 2015).…”
mentioning
confidence: 99%